Grand Challenges in AI and Education Beyond 2030 - Beverly Woolf; Danielle Allessio; Ivon Arroyo; Sai Gattupalli; Boming Zhang (Interaction Design and Architecture(s))
Artificial intelligence (AI) has made large changes in major industries and disrupted or reorganized many disciplines. As a result, traditional educational practices need to be reexamined to enable learners to develop new skills, to manage and utilize new technologies and to increase productivity in a rapidly changing world. A more flexible educational system is required to enable life-long and life-wide upskilling and reskilling. This article provides four grand challenges for AI and education to optimize digital learning, online resources and virtual classrooms. It suggests several problems to address, visions to spur the field forward and strategies that will make teaching and learning more effective. The article also considers ethical use of technology, decreased jobs in some sectors and the possibility that AI will exacerbate an existing deficit in diversity and equity among students.